2019
DOI: 10.20546/ijcmas.2019.803.104
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phytohormones and Other Dormancy Breaking Chemicals on Seed Germination of Inula racemosa Hook F. – A Critically Endangered Medicinal Plant of North Western Himalaya

Abstract: Inula racemosa Hook. f. is commonly called Pushkarmool, belongs to family Asteraceae. The plant is distributed in temperate alpine Himalayas at an altitude of 1,500-4,200m from Kashmir to Kumaon, Afghanistan to Central Nepal. Pushkarmool is commercially a very important medicinal plant of the North Western Himalayas. The plant is used in Ayurveda as an expectorant, rejuvenator and immune modulator. Root powder is reportedly hypoglycemic and hypocholesterolemic in human subjects. The species is critically endan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 5 publications
2
5
0
1
Order By: Relevance
“…A slight increase in soil organic matter can enhance the CEC of the soil to a great extent. The increase in CEC, as a result of incorporation of organic manures into the soil has also been reported by several workers [23][24][25][26]3,27].…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…A slight increase in soil organic matter can enhance the CEC of the soil to a great extent. The increase in CEC, as a result of incorporation of organic manures into the soil has also been reported by several workers [23][24][25][26]3,27].…”
Section: Resultssupporting
confidence: 72%
“…Potassium is the third most essential macronutrient, followed by nitrogen and phosphorus [1][2][3][4]. It plays a crucial role in plant metabolism, such as photosynthesis, translocation of photosynthates, regulation of stomata, activation of plant enzymes and imparts resistance in plant against pest and diseases [5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Outcome of the experiment suggested that mid November sowing had greater potential of plant disease control (17.86%) compared to mid December sowing with plant disease control value of only 15.1%. The significance of date of sowing on leaf blight score was also reported through earlier workers (Bhat et al, 2011;Wani et al, 2018b;Bano et al, 2021;Padder et al, 2021) studied the effect of spot blotch disease severity and reported that early sown crop was less affected by spot blotch than late sown crop. Singh et al (Wani et al, 2018a;Padder et al, 2022) also reported less spot blotch severity in early sown crop than late sown crop.…”
Section: Effects On Disease Incidence and Severitysupporting
confidence: 72%
“…Nutrient imbalance is one of the constraints affecting the productivity of pulses. Nitrogen and phosphorus fertilizers are generally applied but K fertilizer is often ignored by farmers particularly in Asia" [1][2][3][4][5]. Along with nitrogen and phosphorus, potassium is one of the three essential macronutrients, required by plants in relatively large amounts.…”
Section: Introductionmentioning
confidence: 99%